(untitled) (Research, Society and Development, 2020)
The knowledge of the capacity of leaf production, development of the plant in face of different environmental factors, of its morphogenic, physiological and structural characteristics is important for the development of methods that allow a better use of pastures. With that, the objective of this work was to carry out a literature review on forage grasses regarding their morphogenic, structural and agronomic characteristics and the influence of shading levels. When evaluating the results obtained regarding the morphogenic and structural characteristics, it is noted that the contrast between the morphophysiological and agronomic characteristics may be linked to adaptability mechanisms, where even with better physiological responses, there was a decrease in the production of dry matter. Studies are needed to find out whether or not morphophysiological responses are linked to the productive capacity of plants, and furthermore, that studies be carried out to select species with good productive capacity, adaptability to management and adapted to the conditions of climate, temperature and light in the region where they will be cultivated.